Cost-effectiveness of point-of-care C-reactive protein testing to inform antibiotic prescribing decisions. - Oppong, R; Jit, M; Smith, R; Butler, C; Melbye, H; Mölstad, S; Coast, J (2013)
BACKGROUND: Point-of-care C-reactive protein (POCCRP) is a biomarker of inflammation that offers clinicians a rapid POC test to guide antibiotic prescribing decisions for acute cough and lower respiratory tract infections (LRTI). However, evidence that POCCRP is cost-effective is limited, particularly outside experimental settings. AIM: To assess the cost-effectiveness of POCCRP as a diagnostic tool for acute cough and LRTI from the perspective of the health service. DESIGN AND SETTING: Observational study of the presentation, management, and outcomes of patients with acute cough and LRTI in primary care settings in Norway and Sweden. METHOD: Using hierarchical regression, data were analysed in terms of the effect on antibiotic use, cost, and patient outcomes (symptom severity after 7 and 14 days, time to recovery, and EQ-5D), while controlling for patient characteristics (self-reported symptom severity, comorbidities, and health-related quality of life) at first attendance. RESULTS: POCCRP testing is associated with non-significant positive reductions in antibiotic prescribing (P = 0.078) and increased cost (P = 0.092). Despite the uncertainty, POCCRP testing is also associated with a cost per quality-adjusted life year (QALY) gain of €9391. At a willingness-to-pay threshold of €30,000 per QALY gained, there is a 70% probability of CRP being cost-effective. CONCLUSION: POCCRP testing is likely to provide a cost-effective diagnostic intervention both in terms of reducing antibiotic prescribing and in terms of QALYs gained.